2018
DOI: 10.1039/c8ta05488f
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4/MgO nanosheets: light-independent, metal-poisoning-free catalysts for the activation of hydrogen peroxide to degrade organics

Abstract: The bonding between MgO and g-C3N4 in g-C3N4/MgO nanosheets plays a key role in activating H2O2 to degrade organic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…This result was satisfactory in principle compared to that of the currently reported results. 1,7-9 For instance, Ge et al 7 found that methyl orange degradation over g-C 3 N 4 /MgO hardly occurred at pH < 2 and under visible light irradiation. RhB was found here to be more quickly degraded when the initial pH was adjusted to pH 11 using diluted NaOH solution (0.1 M).…”
Section: Optimal Reaction Conditions Over G-c 3 N 4 (Hy-ht)mentioning
confidence: 99%
See 2 more Smart Citations
“…This result was satisfactory in principle compared to that of the currently reported results. 1,7-9 For instance, Ge et al 7 found that methyl orange degradation over g-C 3 N 4 /MgO hardly occurred at pH < 2 and under visible light irradiation. RhB was found here to be more quickly degraded when the initial pH was adjusted to pH 11 using diluted NaOH solution (0.1 M).…”
Section: Optimal Reaction Conditions Over G-c 3 N 4 (Hy-ht)mentioning
confidence: 99%
“…This result was remarkably better than that under other conditions, where the alkaline conditions reinforced the catalytic activity. However, Ge et al 7 reported that $5% of RhB degradation efficiency was lost when the initial pH was increased from 8 to 10. The initial pH had a different inuence on the catalyst adsorption capacity (Fig.…”
Section: Optimal Reaction Conditions Over G-c 3 N 4 (Hy-ht)mentioning
confidence: 99%
See 1 more Smart Citation
“…2] [10,11]. Although transition metal-containing catalysts have achieved good degradation efficiency, their practical applications are limited because of the secondary pollution of dissolved transition metals in the process [12,13]. In order to solve these problems, some researchers have used various porous supporters to load transition metal oxides, which can actually enhance the catalytic performance and reduce the leaching rate of transition metal ions [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Nevertheless, photocatalytic technique requires highly efficient, stable, low-cost and pollution-free photocatalysts. Many semiconductor photocatalysts, such as TiO 2 , [8,9] g-C 3 N 4 , [10] BiVO 4 , [11] ZnO [12] and MoSe 2 , [13] have been widely investigated by researchers. However, poor visible-light absorption, low separation efficiency of photo-induced carriers or weak electron conductivity greatly limits large-scale applications of these single-component photocatalysts.…”
Section: Introductionmentioning
confidence: 99%